Determinant factor of Islamic financial inclusiveness at MSMEs: Evidence from Pekanbaru, Indonesia - Budi Trianto; Rahmayati Rahmayati; Tetty Yuliaty; Tasiu Tijjani Sabiu (Jurnal Ekonomi & Keuangan Islam, 2021)
Purpose – This study aims to analyze the factors that influence the inclusiveness of Islamic finance in MSMEs and its impact on their business performance.Methodology – This research uses the quantitative approach through SEM analysis. Data were collected directly from respondents using an online survey questionnaire. Respondents in this study were MSMEs who had interacted with the Islamic Banking with the total sample size of 98 MSMEs owners.Findings – The results of this study show that the socio-cultural and marketing communication variables have a positive and significant impact on Islamic financial inclusion. Meanwhile, Islamic financial literacy has a positive but insignificant impact on Islamic Financial Inclusion. Although financial literacy does not have a significant impact on Islamic financial inclusion, it has a positive and significant impact on the performance of MSMEs. Another result shows that Islamic financial inclusion has a positive and significant impact on the performance of MSMEs in PekanbaruOriginality – Research related to the Islamic Financial Inclusion in the MSMEs in Pekanbaru, Indonesia is very limited. This study will contribute to the existing literature in the area of Islamic Financial Inclusion and the development of MSMEs.